1970
DOI: 10.1063/1.1693099
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Long Waves on a Liquid Film

Abstract: The equations of motion for three-dimensional long waves on a liquid film are formulated, and the equation for the surface height is derived. The interaction between two- and three-dimensional waves is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 1 publication
1
34
0
Order By: Relevance
“…An extension to three dimensions of the Benney equation was calculated by Roskes. 8 In the very strong surface tension approximation, Sivashinsky and Michelson 9 demonstrated that this equation reduces to the Kuramoto-Sivashinsky equation, which has been shown to present chaotic behavior. Different approximations to the nonlinear surface wave on thin liquid films have been done, for example, by Alekseenko et al, 10 Alekseenko et al, 11 Trifonov,12 and Chang.…”
Section: Introductionmentioning
confidence: 98%
“…An extension to three dimensions of the Benney equation was calculated by Roskes. 8 In the very strong surface tension approximation, Sivashinsky and Michelson 9 demonstrated that this equation reduces to the Kuramoto-Sivashinsky equation, which has been shown to present chaotic behavior. Different approximations to the nonlinear surface wave on thin liquid films have been done, for example, by Alekseenko et al, 10 Alekseenko et al, 11 Trifonov,12 and Chang.…”
Section: Introductionmentioning
confidence: 98%
“…This leads to a single evolution equation for the film thickness h governing the dynamics of the flow at the onset of the instability. Several one-equation models have therefore been proposed to investigate the 3D dynamics of film flows (Roskes 1969;Atherton & Homsy 1976;Roy et al 2002;Saprykin et al 2005). However, for the range of Reynolds numbers where 3D wavy regimes have been reported by Liu et al (1995); Park & Nosoko (2003), one-equation models have been shown to fail, leading either to an underestimation of the wave speeds and heights, or exhibiting unphysical behaviours (Pumir et al 1983;Ooshida 1999;Scheid et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models and numerical simulations for the flow of a thin film of fluid have important applications in industrial and natural processes (Roskes 1969;Ruschak 1985;Moriarty, Schwartz & Tuck 1991;Chang 1994;Grotberg 1994;Schwartz, Weidner & Eley 1995;Decré & Baret 2003). The dynamics of a thin fluid film spreading or retracting from the surface of a supporting liquid or solid substrate has long been an active area of research because of its impact on many technological fields: for example, applications of coating flows (Ruschak 1985) range from a single decorative layer on packaging, to multiplelayer coatings on photographic film; coated products include adhesive tape, surgical dressings, magnetic and optical recording media, lithographic plates, paper and fabrics.…”
Section: Introductionmentioning
confidence: 99%